Metallic nanocrystals with low angle grain boundary for controllable plastic reversibility - Qi Zhu (Nature Portfolio, 2020)
Improving the reversible plastic deformability and damage tolerance of nanosized metals remains challenging. Here, the authors custom-design low angle grain boundaries in metallic bicrystals to achieve controllable plastic reversibility via fully conservative grain boundary migration.